PELAKSANAAN KEGIATAN EKSTRAKURIKULER QASIDAH REBANA MENGGUNAKAN METODE DEMONSTRASI DI MTSN 1 KOTA PARIAMAN (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This study aims to describe the implementation of the qasidah rebana extracurricular activities using the demonstration method at MTsN 1 Kota Pariaman, illustrates student involvement during the activities, and identify supporting and inhibiting factors in the implementation of these activities. The study uses a qualitative approach with a descriptive method. It is conducted at MTsN 1 Kota Pariaman. The research informants include the qasidah rebana extracurricular supervisor and students participating in the activities. Data was collected through observation, interviews, and documentation. Data validity was ensured through triangulation, while data analysis included data reduction, data presentation, and drawing conclusions. Research results show that the implementation of qasidah rebana extracurricular activities using the demonstration method is carried out through four stages, namely preparation, demonstration, practice, and evaluation. Student involvement is seen from their activeness in following the exercises, paying attention to demonstrations, asking questions, and practising the material taught. The implementation of the activities is supported by the competence of the instructors, student motivation, madrasah support, and regular practice sessions, while hindering factors include the limited number of rebana instruments, differences in student abilities, inconsistent attendance, and limited practice time. Thus, the demonstration method helps students understand and practise rebana playing techniques so that the objectives of the extracurricular activities can be achieved.